The hating game [videorecording (DVD)] - Hale, Lucy, 1989-; Stowell, Austin, 1984-; Daunno, Damon; Jackson, Yasha; Cullen, Sean (Actor); Jaffrey, Sakina; Bernsen, Corbin, 1954-; Thorne, Sally, 1981- (Vertical Entertainment, 2022)
Resolving to achieve professional success without compromising her ethics, Lucy embarks on a ruthless game of one-upmanship against cold and efficient nemesis Joshua, a rivalry that is complicated by her growing attraction to him.